PENGELOLAAN DAN PELAPORAN ASET WAKAF PADA LEMBAGA WAKAF DI INDONESIA: STUDI KASUS PADA YAYASAN BADAN WAKAF SULTAN AGUNG - Intan Wijaya; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2015)
This study in regard to research recording of accounting and reporting waqf assetto the Indonesian waqf institution. The main purpose of this study is to investigate the process of recording and reporting the waqf  asset to the Indonesian institution. This research give qualified information to the stakeholder as well as interested parties to explore waqf accounting system. This study was conducted using the qualitative methods through a case study in the Yayasan Badan Wakaf Sultan Agung by interview, analized financial report and related documents obtained directly from the organization.The result showed the unavalaible of accounting system which specific to organize waqf. this thing has been evidenced by the informants explanation who are worked in financial sector. However, this thing would not be an obstacle to the waqf institution as this  institution  applied  accounting  system  based  on  PSAK  45  regarding  Financial Reporting of Non-Profit Entities approaching accounting system for WAQF.